Does Cause-Related Marketing (CRM) really work in the case of stigmatized products? A conceptual framework and implications for CRM campaigns - Eun Mi Lee (Global Business & Finance Review (GBFR), 2016)
This study examines the effect of company-cause congruency on consumer responses to Cause Related Marketing (CRM) programs of stigmatized products. This study also investigates the moderating role of user status and tests a theoretical model of the effects of attitude toward the industry on congruence, consumer perception of company motives, and subsequent company credibility and attitude toward the company. The results show that congruent condition has a significant effect on only the attitude toward the cause. In the user status, users have a more positive industry attitude and stronger perception of altruistic motives for the stigmatized company than non-users. This study also suggests that consumers who have a positive attitude toward the industry perceive CRM programs to be more altruistic and socially responsible, consequently they perceive the company positively and as being credible.
Keywords: 650; Attitude toward the industry; Congruency; Altruistic motives; Cause-related marketing; Stigmatized products